EMPLACEMENT OF PROTEROZOIC MASSIF-TYPE ANORTHOSITE DURING REGIONAL SHORTENING: EVIDENCE FROM THE BOLANGIR ANORTHOSITE COMPLEX (EASTERN GHATS PROVINCE, INDIA) - Dobmeier C. (My University, 2006)
A study of the 933±32-Ma-old Bolangir massif-type anorthosite complex (Eastern Ghats Province, India) yielded strong evidence for anorthosite emplacement during regional shortening, and thereby new insights in massif-type anorthosite formation. Several lines of evidence strongly suggest synchronism of plutonism and regional deformation. First, structures in the country rocks, which imply N-S-directed shortening accompanied by E-W extension, are mirrored by a E-W trending post-magmatic foliation and N-S trending shear zones in the anorthosite complex. Near the intrusion, the foliation in the country rocks becomes parallel to the contact and an internal marginal foliation, and foliation triple points occur in the country rocks. Second, synshortening dikes inside and outside the anorthosite complex are filled with pluton-related melts. Third, ferrodiorites, which are considered late-stage differentiates of the anorthositic pluton, concentrate in tectonic voids at the pluton margin. Some of these occurrences have been affected by the last increments of the regional deformation, but others transect the same structures. Ascent mechanism and significance of the adjacent terrane boundary of the Eastern Ghats Belt for ascent and emplacement of the Bolangir anorthosite complex are discussed. The results of this study imply that emplacement of Proterozoic massif-type anorthosite is not restricted to extensional settings. © Springer-Verlag 2005.
Keywords: DIAPIR; EASTERN GHATS; INDIA; MASSIF-TYPE ANORTHOSITE; PLUTON EMPLACEMENT; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой